FAKTOR YANG MEMPENGARUHI KEIKUITSERTAAN IBU DALAM KELAS IBU HAMIL DI WILAYAH PUSKESMAS SEBANGAR KECAMATAN BATHIN SOLAPAN KABUPATEN BENGKALIS 2023 - Diana, Nana; Agustina, Santi; Aristi, Tiffany Atia (Ensiklopedia of Journal, 2025)
Abstract: Classes for pregnant women are one of the strategic programs in an effort to improve the knowledge, attitudes, and behavior of pregnant women towards safe and healthy delivery. However, the level of participation of pregnant women in this class is still relatively low in various regions, especially in the Sebangar Health Center area. This study aims to identify and analyze the factors that influence pregnant women's visits to pregnant women's classes in the Sebangar Health Center working area. This study used a quantitative approach with a cross-sectional design. Samples were taken by sample random sampling who were registered at the Sebangar Health Center from October to December 2023. Respondents of this study were 92 pregnant women taken by sample random sampling technique. Data were obtained through questionnaires. Data analysis with computerized univariate and bivariate with Chi-Square test (p≤0.05). The results showed 56.5% of pregnant women did not participate in maternity classes. The results of bivariate analysis showed there was a relationship between knowledge (p value = 0.000), mother's attitude (p value = 0.000), husband's participation (p value = 0.000) and the role of health workers (p value = 0.000), with the visit of pregnant women in attending maternity classes at Sebangar Health Center. Conclusion There is a relationship between knowledge, attitude, husband's participation and the role of health workers on the participation of mothers in maternity classes. Suggestions for health workers need to increase socialization to pregnant women about the importance of participating in maternity classes. Provide more interesting, innovative and adaptive material, and create a whatshapp group so that mothers get information about maternal health and the schedule of maternity classes. Advocate to the government, especially Sebangar Village, to facilitate classes for pregnant women.Keywords: Classes for pregnant women, knowledge, mother's attitude, husband's participation and role of health workers.